A Comparative Analysis of Phenolic Compound Quality in Virgin Coconut Oil - Lantemona, Herdianto (Demeter: Journal of Farming and Agriculture, 2023)
Virgin coconut oil (VCO) is derived from fresh coconut fruit and offers numerous health benefits, such as preventing heart diseases, improving digestion, reducing fat accumulation, and more. VCO contains medium-chain fatty acids that are easily digested and metabolized by the body, preventing fat buildup. Additionally, it is rich in antioxidants like tocopherols and beta-carotene, which help prevent premature aging and maintain vitality. The phenolic content in VCO can be influenced by the processing method and the age of the coconuts used. Therefore, this research examined the impact of processing methods on the quality of phenolic content as a product of the pharmaceutical industry. The largest group of phenolic compounds includes tocopherols, sterols, and flavonoids. Phenolic compounds in coconuts are primarily located in the coconut fruit’s epidermis. VCO produced from coconuts with the epidermis or coconut fruit’s outermost layer contains a higher concentration of phenolic compounds compared to VCO produced from coconuts without the epidermis. The research involved defining and refining the problem, formulating hypotheses or tentative answers, drawing conclusions, and conducting meticulous testing of all conclusions to determine their alignment with the hypotheses. In this study, the researchers compared the quality and phenolic compound content of virgin coconut oil (VCO) by sampling from several small and medium enterprises in various regions, specifically in the Island of Sulawesi. The findings revealed that each graph represents the percentage of five samples, depicting various contents, such as water content, free fatty acids, peroxide value, phenolic compounds, and antioxidant activity